Nicotine Bitartrate Reduces Falls and Freezing of Gait in Parkinson Disease: A Reanalysis - Lieberman, Abraham; Lockhart, Thurmon E.; Olson, Markey C.; Smith Hussain, Victoria A.; Frames, Christopher W.; Sadreddin, Arshia; McCauley, Margaret; Ludington, Elizabeth (Frontiers in Neurology, 2019)
Objective: Determine if NC001, an oral formulation of nicotine that reduces levodopa-induced dyskinesias (LIDs) in MPTP-Parkinson monkeys, could reduce falls, freezing of gait (FOG), and LIDs in Parkinson disease (PD) patients. Methods: Previously collected data from a study analyzing the effects of NC001 on LIDs in PD patients was reanalyzed. Because indirect-acting cholinergic drugs are sometimes helpful in reducing falls, we hypothesized that NC001, a direct-acting cholinergic agonist, could reduce falls in PD. The original 12-center, double-blind, randomized trial enrolled 65 PD patients. NC001 or placebo was administered 4 times per day for 10 weeks, beginning at 4 mg/day and escalating to 24 mg/day. Assessments included the Unified Dyskinesia Rating Scale (UDysRS) and Parts II-III of the original Unified Parkinson’s Disease Rating Scale (UPDRS). Results: Randomization (1:1) resulted in 35 patients on NC001 and 30 on placebo at baseline. Thirty and 27 patients, respectively, had data available for an intent-to-treat analysis. NC001 was safe and well tolerated. After 10 weeks, NC001 patients (14/30) had a significant reduction in falls versus placebo patients (3/27) (p=0.0041) as assessed by UPDRS Part II. NC001 patients (12/30) also had significantly reduced FOG versus placebo patients (4/27) (p=0.0043). NC001 patients, compared with placebo patients, had a significant improvement (p=0.01) in UDysRS ambulation subtest (40% vs 3%, respectively). Although NC001 patients had a greater reduction in dyskinesias on the UDysRS than placebo patients (30% vs 19%, respectively), this was not significant (p=0.09). Conclusions: NC001 significantly improved two refractory symptoms of PD, falls and FOG. The reduction in falls and FOG is attributed to selective stimulation of nicotinic receptors. Clinical Trial: Conducted under IND 105, 268, serial number 0000. ClinicalTrials.gov identifier NCT00957918.